HUBUNGAN KEHARMONISAN KELUARGA DENGAN KONSEP DIRI SISWA - Nurhasnah (Perspektif Pendidikan dan Keguruan, 2021)
This research was motivated by various problems experienced by students to form and develop self-concepts. Family harmony and socioeconomic status are factors that are thought to influence the development of students' concepts. This study aims to describe: (1) family harmony, (2) the self-concept, (3) relationship of family harmony with self concept. This research uses quantitative methods of descriptive type correlational. The research population is 332 students of SMAN 1 Rao Pasaman. A sample of 182 students, selected with Proportional Stratified Random Sampling. The instrument used is model likert scale. The study findings showed that: (1) student family harmony is in a harmonious category with a percentage of 77.55% of the ideal, (2) the self-concept of the student's is in a positive category with a percentage of 68.88% of the ideal, (3) there is a positive and significant relationship between family harmony and self-concept, the contribution of family harmony to the self -concept is 19%. This means that family harmony variables can be used as predictors to predict self-concept.